Penggunaan Teori Argumentasi terhadap Penegakan Hukum Pecandu dan Penyalahgunaan Narkotika - Listyowati Sumanto; Rizka Anugrah Azhari (Syntax Corporation Indonesia, 2024)
Law enforcement against drug crimes is mostly done by law enforcement agencies, and offenders convicted by the courts serve sentences in prisons. Law enforcement is not a definitive action, but the implementation of a definitive action, namely the application of a right to an event, which can be likened to drawing a straight line between two points. Normative legal research is carried out to produce arguments, theories or new concepts as prescriptions in solving the problems faced. The substance of the narcotics law has not provided a clear picture of the application of the law to drug users who use drugs for themselves, who qualify as drug addicts and victims. Law enforcement against drug addicts and users according to Law Number 35 of 2009 concerning Narcotics includes non-penal policy countermeasures, namely pre-emptive (counseling) and preventive (prevention) efforts. Penal policy countermeasures focus more on repressive actions (direct enforcement). Repressive (direct enforcement) carried out by the Police to provide a deterrent effect for perpetrators of drug crimes. There are 2 (two) obstacles faced by the Muna Resort Police Drug Unit, namely non-penal policy barriers and penal policy obstacles.